From Enantiopure Hydroxyaldehydes to Complex Heterocyclic Scaffolds: Development of Domino Petasis/Diels–Alder and Cross‐Metathesis/Michael Addition Reactions. Issue 38 (5th August 2014) - Cannillo, Alexandre; Norsikian, Stéphanie; Tran Huu Dau, Marie‐Elise; Retailleau, Pascal; Iorga, Bogdan I.; Beau , Jean‐Marie
Abstract One‐step assembly of hexahydroisoindole scaffolds by a sequence that combines the Petasis (borono‐Mannich) and Diels–Alder reactions is described. The unique selectivity observed experimentally was confirmed by quantum calculations. The current method is applicable to a broad range of substrates, including free sugars, and holds significant potential to efficiently and stereoselectively build new heterocyclic structures. This easy and fast entry to functionalized polycyclic compounds can be pursued by further transformations, for example, additional ring closure by a cross‐metathesis/Michael addition domino sequence.